Producing a socially accountable medical school: AMEE Guide No. 109. (1st November 2016) - Boelen, Charles; Pearson, David; Kaufman, Arthur; Rourke, James; Woollard, Robert; Marsh, David C.; Gibbs, Trevor
Abstract: Health systems worldwide are confronted with challenges due to increased demand from their citizens, an aging population, a variety of health risks and limited resources. Key health stakeholders, including academic institutions and medical schools, are urged to develop a common vision for a more efficient and equitable health sector. It is in this environment that Boelen and Heck defined the concept of the "Social Accountability of Medical Schools" – a concept that encourages schools to produce not just highly competent professionals, but professionals who are equipped to respond to the changing challenges of healthcare through re-orientation of their education, research and service commitments, and be capable of demonstrating a positive effect upon the communities they serve. Social Accountability calls on the academic institution to demonstrate an impact on the communities served and thus make a contribution for a just and efficient health service, through mutually beneficial partnerships with other healthcare stakeholders. The purpose of this Guide is to explore the concept of Social Accountability, to explain it in more detail through examples and to identify ways to overcome obstacles to its development. Although in the Guide reference is frequently made to medical schools, the concept is equally applicable to all forms of education allied to healthcare.